PENERAPAN PERATURAN BUPATI NAGAN RAYA NOMOR 13 TAHUN 2015 TENTANG PEDOMAN PEMBANGUNAN GAMPONG - Nellis Mardhiah; Yurilawati Yurilawati (Prodi Ilmu Hukum, Universitas Teuku Umar, 2018)
Regent of Regulation Number 13 Year 2015 About Guidelines for Gampong Development It is a legal produ of Nagan Raya District Government in the successful implementation of development in accordance with the obligation in village law No. 6 of 2014. This study aims to determine the success of Gampong government in carrying out development in accordance with applicable rules in Nagan Raya District. The intended implementation is based on the conceptual approach of George Edward III. This research uses qualitative research with descriptive approach which can give actual picture in the field based on the prevailing regulation. The results showed that the guidelines for the implementation of regents regulation has not been maximally run by all Gampong government due to the weakness of socialization and not supervise inherent in the development plan with the actualization of the program in accordance with the scale of national development planning. And internally, the gampong government in the Nagan Raya government area is still the weakness of the empowerment of the village apparatus in self-actualization of the human resources capability, so that the planning of village development can not utilize the use of location and the utilization of space and land in the dimension of development continuously.Keywords: village development, regent of regulation